Charismatic Leadership Based on Student Friendly Learning Approach - A. Ishaq Fauzi Al-Fauzany; Engkus Kuswarno; Ikka Kartika AF; Uyun Supyan Sauri (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
The burden of responsibility to be the figure head of Pondok Pesantren in ensuring the quality of learning that many are faced with the challenge-the challenge of change civilization. Need a high loyalty, integrity full, is able to provide the best individual performance of the Leader of the multi-talented, in educating students with heartfelt, sincere, be personal loved ones and have an attraction worthy of being a role model to all people, be uswah at once has an example in life.. Dissertation using Qualitative Methods, the study about research are descriptive and tend to use the analysis. The process and the meaning is accentuated in qualitative research. The foundation of the theory be used as a guide in order to focus the research in accordance with the facts in the field. The results showed that, of charismatic leadership on a figure Kyai is a skill that consists of a art print life skills of the students and the art of managing a team of educators. Not just the skills to manage an organization, but must be coupled with the ability to supervise, direct, and motivate, in a way that is efficient and effective. Leadership that gives the effect of depth and incredible to motivate their followers in achieving the performance of the ideal. Theory-based Learning friendly students is the process of transper material science and the transformation of implementation science that is adapted to the capacity of students to more easily follow and apply them in real life. Between the Caregiver as the executor of education should be able to mengkulturasikan with primary sources that are used as a reference science students as a provision sailing on life. The Kyai/Sitter Boarding school Fauzan Sukaresmi Garut as well as the elements of Management of a charismatic figure of the presence of the self they are required to master the five basic competence i.e. the Competences of the Spiritual, Personality Competence, Competency Management, Entrepreneurship Competency, Competence, Supervision, and Social Competence.